Production of vitamin B2 (Riboflavin) - Мельник Роман Володимирович (European Research Materials, 2024)
Riboflavin (also known as vitamin B2 or lactoflavin) is very important for human health and vitality, one of the B group, which, like many others, is water-soluble. It is naturally present in some food products, and is also available as a dietary supplement. This nutrient was removed from the group of B vitamins in 1933, as a yellow element resistant to high temperatures. It is a component of two major coenzymes: flavin mononucleotide (also known as riboflavin 5'-phosphate) and flavin adenine nucleotide, which play a major role in energy generation as well as in the synthesis of other B vitamins. Humans should consume vitamin B2 every day , because the body can store only a small amount of it, and the reserves are quickly depleted. Riboflavin is one of the most common vitamins, present in all animal and plant cells, and is widely used in agriculture. Although riboflavin deficiency is rare in developed countries, in Ukraine, due to the difficult socio-economic situation, the population does not always have access to high-quality products rich in this vitamin. This can negatively affect people's health, making the issue of microbiological synthesis of riboflavin relevant. There are several dozen producer microorganisms that produce riboflavin. Microbiological synthesis has significant advantages compared to chemical synthesis, in particular, the possibility of synthesis of complex organic compounds in mild conditions (low temperature, low pressure), the use of cheap raw materials, often obtained from industrial waste. In the chemical manufacturing process, the products are usually mixtures that must be carefully purified to obtain highly purified vitamins. This, in turn, increases the time required to achieve the required amount of vitamin. In particular, the producer of riboflavin can develop in simple nutrient media, semi-products and food industry waste. In addition, biomass is an important source of feed protein, which makes production virtually waste-free. The production of food additives all over the world shows stable growth both in terms of quantity and quality. This growth is about 15% in Asia, 4.4% in the United States and 12% in European countries. The free circulation of safe and high-quality food products is a key element of the internal market, because it contributes to the strengthening of people's health and well-being, as well as their social and economic interests both in Ukraine and abroad. EU policy towards other states should ensure a high level of protection of life and health of people in Ukraine. Regulation of the European Parliament and the Council of the EU No. 1333/2008 of December 16, 2008 was developed to ensure the effective functioning of the internal market, guaranteeing a high level of protection of human health and consumers